What is the role of radiological testing of lower esophageal sphincter function?. Issue 1 (6th August 2016) - Scharitzer, Martina; Pokieser, Peter
Abstract : Radiological fluoroscopic evaluation remains the primary imaging modality of choice to evaluate patients with swallowing disorders, despite the increasing availability and technical advantages of nonradiological techniques and the current radiological focus on cross‐sectional imaging studies, such as computed tomography and magnetic resonance imaging. The radiological swallowing evaluation should be tailored to assess the entire upper gastrointestinal tract, including the lower esophageal sphincter. Fluoroscopy enables the simultaneous assessment of esophageal motility disorders, as well as structural pathologies, including strictures, webs, rings, diverticula, and tumors. Mono‐ and double‐contrast esophagrams and solid bolus tests together allow assessment of lower esophageal sphincter function and complement other methods, such as endoscopy, manometry, or impedance planimetry. Here we review the role of radiological studies for correct assessment of structural and functional pathologies at the level of the lower esophageal sphincter.